Time for a new political regime typology? A vectoral classification to address intraregime shifts and international dynamics - Den Bosch, Jeroen van (Teorija in praksa, 2024)
This article proposes a novel typology for classifying political regimes, addressing the limitations of previous models by incorporating three organisational nexuses (party-organisations, militaries, tutelary bodies) and three vectoral dimensions (tyranny, ideology, multipartyism). This approach allows for a dynamic understanding of regime behaviour, capturing intra-regime shifts without requiring reclassification. The typology innovatively distinguishes between personalist regimes, ideocracies, and hybrid forms, providing a nuanced framework for analysing contemporary and historical political systems. By integrating ideology back into the analysis and offering a comprehensive measure of tyranny, this classification enhances our ability to study regime resilience, autocratisation, and democratisation, as well as how political regimes collaborate and learn in the international system.
Keywords: authoritarianism; avtoritatizem; dictatorship; diktatura; ideologija; ideology; personalism; personalizem; pluralism; pluralizem; Politični sistemi; tiranija; totalitarianism; totalitarizem; tyranny; Vektorska analiza